Guatemala : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Guatemala. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2021)
Guatemala has managed to keep infections and deaths moderate during the pandemic. The economic impact of COVID-19 has been mild given an early reopening of the economy, unprecedented policy support, and resilient remittances and exports. However, despite large-scale government interventions to support households, poverty and malnutrition have deteriorated following COVID-19 and the two major hurricanes battering Guatemala last November.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Guatemala